Optimalisasi Laporan Kegiatan Penanaman Modal bagi Usaha Kecil dan Menengah di DMPTSP Kota Serang - Sri Ayadilah Akhdzulhijah; Anti Wulan Agustini (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
Community service is one of the implementations of the Tri Dharma of Higher Education which aims to provide real contributions to society through the application of science and technology. This activity aims to improve the understanding of small and medium enterprise (SME) actors regarding the preparation of Investment Activity Reports (LKPM) at the Investment and One-Stop Integrated Service Office (DPMPTSP) of Serang City. The problem found in the field indicates that many business actors still do not fully understand the procedures for preparing and submitting investment activity reports. The method used in this activity is a descriptive method with a mentoring approach carried out through observation, socialization, and direct assistance to business actors. The results show an increase in the understanding of business actors regarding the importance of investment activity reports and their ability to prepare reports more systematically. This activity is expected to increase business actors' awareness of their reporting obligations and support the creation of more orderly and transparent investment management.